Fragmented Legal Protection in Child Marriage Prevention: Intersections of State Law, Religious Norms, and Local Values in East Java - Lukman Santoso; Khaidarulloh Khaidarulloh; Muh Jihad Al Haqiqi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2026)
This article aims to explore the ambiguity in the implementation of policies to prevent child marriage in East Java. Although Law No. 16 of 2019 has raised the minimum age for marriage, the number of requests for marriage dispensations remains high. This legal research uses a socio-legal approach and normative-empirical analysis of the discourse on preventing child marriage in East Java. Using Clifford Geertz's broker-culture theory, this study captures how religious elites and local figures act as cultural brokers who bridge and transform the meaning of national legal norms into the value framework of local communities. Boaventura de Sousa Santos' theory of interlegality helps map the overlap between state law, religious law, and customary norms that form a hybrid legal structure in the practice of granting marriage dispensations. This study finds that the misalignment between national law, local norms, and socio-religious authorities has led to fragmented legal protection for children. This situation is exacerbated by the absence of effective binding local regulations and the state's weak capacity to intervene in religious discourse and social practices surrounding child marriage. This study contributes to an inclusive-collaborative approach to preventing child marriage through a framework of legal glocalisation, namely: proactive policies, integrated empowerment, and equal multi-stakeholder synergy, including local governments, the Ministry of Religious Affairs, health workers, peer counsellors, families, civil society, the Indonesian Ulema Council (MUI), and religious leaders.